Preprocessing of powder to enhance mechanical and thermal response of bulk magnesium. Issue 3 (May 2019) - Tekumalla, Sravya; Si Chun, Lim; Gupta, Manoj
Abstract: This article investigates the effect of preprocessing of powders on improving the properties of pure bulk magnesium synthesized via microwave assisted powder metallurgy method. Preprocessing was done by compacting the powder prior to primary processing (cold compaction & microwave sintering) and secondary processing (hot extrusion). Various characterization studies were conducted to determine the microstructural features, temperature governed properties and mechanical properties. Results revealed that preprocessing (compaction) led to improved properties i.e. higher yield strength, better grain refinement and higher resistance to ignition.